Using combined proteins and hydrocolloids for creating aerated candy masses - Калинівська, Тетяна Віталіївна; Оболкіна, Віра Іллівна (Eastern-European Journal of Enterprise Technologies, 2014)
The paper deals with studying the functional and technological properties of whey proteins, combined mixtures of whey protein concentrate and egg-whites, additional stabilizers such as gelatin and gum arabic. The influence of combined protein and hydrocolloid systems on forming structural properties of aerated candy masses such as "soft nougatines" with increased aggregate stability is determined. Theoretical data on functional and technological properties of proteins and hydrocolloids are given. The technological factors, influencing foam formation and foam stability are considered. Experimental data on the influence of sugar, gelatin hydrocolloids and gum arabic on the structure and properties of foams are given in the paper. Analyzing these data, the authors have concluded that adding sucrose-glucose syrup to protein foams increases the foam formation of the system. In addition, the positive effect of sugars is caused by the increased viscosity of the bulk phase that reduces the rate of water loss by lamellae and increases the system stability. Adding complex mixtures of gelatin - gum arabic have a high stabilizing effect due to reducing the surface tension and creating aggregation-resistant layers of the dispersion medium. Owing to such laws, the authors have confirmed the possibility of stabilizing the properties of multi-component disperse systems of aerated candy masses. The data, given in the paper, show the possibility of further studying of whey protein concentrate properties. Using the combined protein and hydrocolloid system attracts interest when creating a new range of aerated candy masses with the original structure.